Rise of non-standard policy Instruments: Can budgeting catch up? - Moretti, Delphine (OECD Publishing, 2023)
For implementing their economic and social policies, governments have traditionally relied on direct spending but increasingly use "non-standard" policy instruments, such as loans and guarantees. However, in many OECD countries, loans and guarantees are not yet submitted to the same scrutiny than direct spending as part of the budget process, and future costs associated with the use of these policy instruments are often not estimated, nor provisioned, making them appear initially costless. In turn, this generates risks of potentially biased budgetary decision making, deviations from medium-term spending plans and limited transparency. Considering experiences of OECD countries, this paper advises that budget offices take a leading role in proposing budgetary treatments for loans and guarantees that ensure an even-level playing field with traditional spending and put considerations of efficiency of spending above optimisation of short-term fiscal outcomes